Changes in Mental Health of Women Undergoing Assisted Reproductive Technology Treatment During the COVID-19 Pandemic Outbreak in Xi'an, China - Qu, Pengfei; Zhao, Doudou; Jia, Peng; Dang, Shaonong; Shi, Wenhao; Wang, Min; Shi, Juanzi (Frontiers in Public Health, 2021)
Objective: To investigate the mental health of women undergoing assisted reproductive technology (ART) treatment during the novel coronavirus pneumonia (COVID-19) pandemic outbreak in Xi'an, China. Methods: A repeated cross-sectional study was administered to women undergoing ART treatment during the outbreak period (599 women in February 2020) and the control period (892 women in May 2020) at the Northwest Women's and Children's Hospital, Xi'an, China. Results: Both the ART-treated women surveyed during the outbreak period and those surveyed during the control period had high scores on the fear dimension (0.88, 0.51). The total scores for mental health among the participants during the control period were lower than those during the outbreak period (difference = −0.22; 95% CI = −0.25, −0.18). Lower scores were also seen during the control period, compared to those in the outbreak period, for depression (difference = −0.18; 95% CI = −0.23, −0.13), neurasthenia (difference = −0.31; 95% CI = −0.36, −0.25), fear (difference = −0.37; 95% CI = −0.43, −0.31), compulsion anxiety (difference = −0.13; 95% CI = −0.16, −0.09), and hypochondriasis (difference = −0.09; 95% CI = −0.12, −0.06). Conclusions: During the COVID-19 global pandemic, the mental health of women undergoing ART treatment in Xi'an, China, was primarily manifested as fear. As the pandemic was brought under control, the mental health of ART-treated women improved. As evidenced by these results, the COVID-19 pandemic influences the mental health of women undergoing ART treatment, and clinicians should be aware of this for similar future situations.